Challenges in Harmonizing AI-Enabled Smart Contracts with the General Principles of Contract Law in the Iranian Legal System: A Digital Governance Perspective - Kaboudjai, Hamid (AI and Tech in Behavioral and Social Sciences, 2026)
This study examines the challenges of harmonizing AI-enabled smart contracts with the general principles of contract law in the Iranian legal system from a digital governance perspective. Unlike purely blockchain-based smart contract code, AI-enabled smart contracts may involve algorithmic tools in contract drafting, party verification, oracle-based factual assessment, performance monitoring, risk scoring, or dispute-resolution support. This distinction is central because ordinary smart contract code is typically deterministic, whereas AI systems may generate probabilistic or adaptive outputs that complicate the attribution of consent, responsibility, and legal effect. The study adopts a doctrinal and descriptive-analytical method, relying on Iranian statutory materials, contract-law doctrine, selected comparative scholarship, and leading literature on smart contracts, blockchain governance, and algorithmic accountability. The analysis shows that smart contracts may fall within the scope of Iranian contract law when they operate as electronic instruments for expressing and executing human intention. However, serious challenges remain regarding the verification of legal identity and capacity in pseudonymous blockchain environments, the formation of informed consent through code, the uncertain legal status of cryptocurrencies and tokenized assets, the tension between automated execution and mandatory legal rules, and civil liability for technical or algorithmic failures. The study argues that effective recognition of AI-enabled smart contracts in Iran requires a layered governance model: reliable digital identity mechanisms, human-readable contractual terms accompanying executable code, clear rules on digital assets, auditable and legally responsive code architecture, professional standards for developers, and judicial or arbitral mechanisms capable of reviewing technical execution without undermining innovation. These reforms can help integrate smart contracts into Iran’s legal system while preserving contractual justice, public policy, and legal certainty.